Current status of sweet orange (Citrus sinensis L.) orchards in the River Nile State, Sudan - Mekki, Mohammed H.; Elamin, Osman M.; Elkashif, Mohamed E. (Gezira Journal of Agricultural Science; Vol 14 No 2 (2016), 2016)
ABSTRAC     Production of sweet oranges in the Sudan does not cover domestic needs and sweet oranges are currently imported from Egypt, Iran and South Africa to satisfy the increasing demand. Hence, there is a need to investigate factors involved in the decline of sweet orange trees in one of the most important States for orange production in the Sudan. This research aims to study and evaluate different agronomic practices contributing to the prevailing sweet orange performance in the River Nile State, Sudan. A questionnaire and interviews with 120 sweet orange growers from Ketiab, Zeidab and Gandato citrus projects indicated that 75.8% of the farmers have orchards less than 2.9 ha. Low yielding cultivars such as “Sinnari”, the local selection (Baladi), Hamlin and Nori 16 dominate in the areas, 96.7% of the trees were budded on sour orange rootstocks, 85.8% of the seedlings were budded in private nurseries using bud wood collected from non-certified mother trees from private orchards. All sweet oranges were grown with other fruit species in 100% of the orchards, 80.8% used flat surface irrigation. There is no fixed fertilizer program. The type and quantity of chemical and organic fertilizers varied with different growers. No foliar fertilizers were used and nutrient deficiencies of Zn, Fe and Mn were observed in most orchards. Extension services for citrus production are highly needed for improvement of yield and quality of sweet oranges in the River Nile State